2021
DOI: 10.31332/lifalah.v6i1.2482
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Identity Index and Financial Performance of Islamic Banks in Asia

Abstract: This study is a follow-up study conducted by Zaki et al. (2014), who explored Islamic banks' ethical identity with financial performance. This study aims to identify the identity of Islamic banks in Asia against Shari'ah law and examine the relationship between EII and financial performance. The data used are financial data from 7 Islamic banks in Asia in 2016-2019. The study results show that the higher the EII value, the higher the Islamic bank supervision of sharia. Then the researcher describes the relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…The findings of this study are consistent with research that shows that disclosing one's Islamic ethical identity has a considerable impact on financial performance (Marka & Serly, 2020;Rahman et al, 2014;Sumiyati & Vebtasvili, 2021;Zaki et al, 2014), despite the fact that the study (Al-Homaidi et al, 2020b;Alhammadi et al, 2020) found no connection between financial performance and the declaration of Islamic ethical identity. Further, implementing labor standards that are consistent with Islamic ethics will significantly boost the company's growth (Marka & Serly, 2020).…”
Section: Figure 2 Path Analysis Modelsupporting
confidence: 89%
See 3 more Smart Citations
“…The findings of this study are consistent with research that shows that disclosing one's Islamic ethical identity has a considerable impact on financial performance (Marka & Serly, 2020;Rahman et al, 2014;Sumiyati & Vebtasvili, 2021;Zaki et al, 2014), despite the fact that the study (Al-Homaidi et al, 2020b;Alhammadi et al, 2020) found no connection between financial performance and the declaration of Islamic ethical identity. Further, implementing labor standards that are consistent with Islamic ethics will significantly boost the company's growth (Marka & Serly, 2020).…”
Section: Figure 2 Path Analysis Modelsupporting
confidence: 89%
“…Islamic banks' financial performance in Asia, as measured by a scale of ROA and ROE, is impacted by the declaration of Islamic ethical identity (Ariyanto, 2014). Increased investment in Islamic banking will be influenced by the disclosure of a credible Islamic ethical identity and fully disclosed information, which will increase investor satisfaction and encourage continued investment in Islamic banking, which will improve the company's financial performance with an increase in additional capital (Sumiyati & Vebtasvili, 2021). H3a: Islamic corporate governance affects positive financial performance through disclosure of Islamic ethical identity…”
Section: Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research on the influence of CEI on Islamic banks or companies was conducted by Awwal et al (2023), Sukardi et al (2022), Sumiyati & Vebtasvili (2021), and Mutmainah & Apriliantika (2023). The novelty in this research is the focus on company culture that begins to implement sharia principles, and what distinguishes it from the mentioned study is the utilization of the ownership structure concept as a moderating variable.…”
Section: Introductionmentioning
confidence: 93%